Mandibular Carnassial Tooth Malformations in 6 Dogs—Micro-Computed Tomography and Histology Findings - Ng, Kevin K.; Rine, Stacy; Choi, Eunju; Fiani, Nadine; Porter, Ian; Fink, Lisa; Peralta, Santiago (Frontiers in Veterinary Science, 2019)
Objective: To document the clinical, radiographic, and histological characteristics of mandibular first molar teeth with developmental abnormalities previously attributed to dens invaginatus and enamel pearls in dogs. Materials and methods: Affected mandibular first molar teeth from dogs were evaluated grossly and via intraoral radiography. Endodontically and/or periodontally compromised teeth were extracted and subjected to some combination of micro-computed tomography, histopathology, and immunohistochemistry with anti-amelogenin antibody. Results: Six dogs with developmental abnormalities of mandibular first molar teeth were identified, representing 11 affected teeth. The condition was bilateral in 5 dogs, while in 1 dog, only one mandibular first molar tooth was present. Patient weight ranged from 1.7 to 6 kg (median = 4.09 kg). On intraoral radiographs, root convergence or parallelism was noted in 6 of 11 teeth, and root dilaceration was noted in 3 of 11 teeth. Eight teeth required extraction due to periapical lucencies or periodontitis. On micro-CT, the abnormal teeth were characterized by the presence of abnormal, heterogenous hard tissue with beam attenuation characteristics midway between that of enamel and dentin. Enamel fissures were identified in 4 of 8 teeth, while ectopic radicular enamel was identified in 2 of 8 teeth. The abnormal tissue was traversed by channels measuring 20-40um in diameter. Channels communicated with the enamel fissures in 2/8 teeth, the furcation in 2/8 teeth and the pulp in 4/8 teeth. The abnormal tissue was frequently surrounded by disorganized dentin. Histologic features of enamel and dentin were absent from the abnormal tissue and immunohistochemistry to detect amelogenin in the abnormal tissue was negative in all samples. Conclusion: The dental abnormalities described here correspond to a previously unrecognized developmental abnormality involving the mandibular first molar teeth in dogs. The developmental origin of the abnormal tissue could not be ascertained, and further investigations are required to determine the mode of formation, origin of the abnormal tissue, and factors associated with development. These developmental abnormalities more closely resemble molar-incisor malformation, rather than dens invaginatus or enamel pearls as described in humans. The authors propose that affected mandibular first molar teeth simply be referred to as having carnassial tooth malformations.